Transforming the Role of Women Farmers and of Refugees: Two Italian Experiences of Social Innovation in Mountain Areas - Elisa Ravazzoli; Cristina Dalla Torre; Thomas Streifeneder (Revue de Géographie Alpine)
Global trends such as international migration and large-scale agriculture are having an impact on the economy and society of Italy’s mountain territories. Socio-economic challenges call for new solutions that existing public institutions and private local organizations fail to address properly. Social innovation (SI) has become a relevant paradigm to address social challenges. By reconfiguring existing social practices, it introduces new solutions (e.g. services, practices, cooperation models) to better respond to social needs, improving the wellbeing of mountain areas. In the paper, two initiatives were selected that target empowerment of vulnerable groups (refugees and women farmers). Using the agency-structure framework, an explorative study of these initiatives has been conducted to analyse the process of reconfiguring social practices, the outcomes, and the factors that may enable and hinder the initiatives. The results show that social innovation has transformed the meaning of cultural symbols and the socio-economic roles of the target groups, leading to an improvement of the whole community’s wellbeing.